Atividade do músculo esternocleidomastóideo em crianças com displasia broncopulmonar - Matos, Lucas Boaventura de (2019)
Introduction: Bronchopulmonary dysplasia (BPD) is a chronic lung disease that usually affects preterm infants (PI) who require oxygen for more than 28 days. Although studies have shown alterations in lung function in infants with BPD, there is no evidence of the behavior of accessory respiratory muscles in the first years of life and over time in these infants. In this context, our hypothesis is that infants with BPD present accessory respiratory muscle involvement, specifically in the sternocleidomastoid (SM), during the first three years of life. Objective: To compare SM muscle activity in infants diagnosed with BPD during the first three years of life. Materials and methods: A longitudinal observational analytical study involving 21 infants divided into three groups: 7 preterm infants with BPD; 7 preterm infants without BPD (GPT) and 7 infants control group (CG) all term healthy. The electrical activity of SM was evaluated by surface electromyography (sEMG) at the end of the first and throughout the third year of life. For the collection of sEMG, the infants were awake and in spontaneous breathing, they were placed in a supine position on a stretcher, not moving the head for 23 seconds during the collection of the signal. The variables analyzed were: frequency with the highest power reached in the spectrum (Fpico), average frequency of the collected signal (Fmedia), frequency at 80% (F80) and median frequency of the spectrum (F50). They were evaluated in the two moments of data collection, inter and intra groups. The statistical software R was used for statistical analysis, the Mann-Whitney test being used for intragroups and Wilcoxon for intergroups. A significant p-value level of less than 0.05 was considered. Results: It was observed that infants in the GDBP group had a reduction in electromyographic activity both in relation to intra-group and inter groups of infants over time in relation to Fpico, Fmedia, F80 and F50 (p = 0.00). Conclusion: We observed a decrease in the frequency of triggering of action potentials of SM motor units in the GDBP group over time, which may be indicative of muscle fatigue. Other long-term follow-up studies for respiratory muscle evaluation in BPD infants should be performed. Key words: Respiratory muscles, Preterm, Bronchopulmonary dysplasia, Surface electromyography.